Modified occlusal technique using intraoral periapical film: An alternative approach - Sneha H Choudhary; Lata M Kale; Sunil S Mishra; Narendra B Supe; Nilofar S Zaidi; Narayan D Pandey (Wolters Kluwer Medknow Publications, 2018)
Most common and difficult problem while taking intraoral periapical radiographs in the posterior region of the jaw is gagging. Thus, in an attempt to obtain the radiographs of maxillary and mandibular third molar without causing much discomfort and additional financial burden to the patient, an alternative technique was devised. This technique requires a dental chair, intraoral dental X-ray machine, regular size 2 periapical film, and artery forcep. The film is placed parallel to the occlusal plane as in case of occlusal radiography with the embossed dot side facing towards the teeth to be radiographed and exposures are made. The resulting radiographs showed complete image of third molars without causing stimulation of gag reflex and without superimposition of zygomatic process on roots of maxillary third molars. Thus, the present technique can be used satisfactorily for taking third molar radiographs in patients with severe gag reflex.